The politics of life itself: biomedicine, power, and subjectivity in the twenty-first century - Rose, Nikolas (In-Formation, 2009)
For centuries, medicine aimed to treat abnormalities. But today normality itself is open to medical modification. Equipped with a new molecular understanding of bodies and minds, and new techniques for manipulating basic life processes at the level of molecules, cells, and genes, medicine now seeks to manage human vital processes. The Politics of Life Itself offers a much-needed examination of recent developments in the life sciences and biomedicine that have led to the widespread politicization of medicine, human life, and biotechnology. Avoiding the hype of popular science and the pessimism of most social science, Nikolas Rose analyzes contemporary molecular biopolitics, examining developments in genomics, neuroscience, pharmacology, and psychopharmacology and the ways they have affected racial politics, crime control, and psychiatry. Rose analyzes the transformation of biomedicine from the practice of healing to the government of life; the new emphasis on treating disease susceptibilities rather than disease; the shift in our understanding of the patient; the emergence of new forms of medical activism; the rise of biocapital; and the mutations in biopower. He concludes that these developments have profound consequences for who we think we are, and who we want to be.